Towards More Equitable Urban Greening: A Framework for Monitoring and Evaluating Co-Governance - Eleanor Chapman; Viktor Bukovszki; Martina van Lierop; Silvia Tomasi; Stephan Pauleit (Urban Planning)
Urban greening has grown in significance in Europe and worldwide as a presumed “public good” initiative, delivering a range of benefits for human health and wellbeing. To redress inequalities in the distribution of such benefits, attention has turned to the potential of collaborative governance. Indicator-based frameworks have also begun to receive attention for their ability to monitor and evaluate not only the performance of greening interventions, but also the policies, practices, and norms that influence their planning and implementation, with a view to transforming governance arrangements. Extensive sets of indicators have been proposed in the literature; however, few studies have addressed the process of adapting monitoring frameworks to the limited resources and highly specific conditions of local government. We address this gap by providing an account of an early phase in developing and contextualising a framework to assess governance of urban greening in seven European cities. Following review of existing indicator sets and literature related to co-governing urban green space, we compiled a set of 126 indicators and clustered these according to normative principles underpinning successful co-governance. We then worked with city representatives to contextualise a subset of 80 indicators and link them to relevant objectives. We found that organising indicators according to principles and applying the criteria of relevance and feasibility was useful to make an abstract concept operational and to promote strategic thinking. However, we also found evidence of likely barriers to using indicators in practice, chief among them the limited agency of responsible staff, with implications for the potential to politicise indicators and thereby guide transformative change.